Learning With Error for Digital Image Encryption - Setiawan, Aisyah Nooravieta; Wijayanti, Indah Emilia; Isnaini, Uha (Journal of Fundamental Mathematics and Applications (JFMA), 2024)
Learning With Error (LWE) is one of the development of a system linear equation that add some noise or error. These problems have good potential for cryptography, especially for the development of Key Exchange Mechanism (KEM). Moreover, the question is whether LWE can be applied for digital image security or not. The digital image consists of hundreds of pixels that can be interpreted as a matrix. Each Pixel is encrypted with LWE so that the image becomes unidentified or cipher.